PENGARUH MODEL PEMBELAJARAN DIFFERENTIATED BASED LEARNING (DBL) TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 18 MAKASSAR - Rustam, M; Bunyamin, Andi; Mustamin; Syahid, Akhmad; Azhar Burhanuddin, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Differentiated Based Learning (DBL) model on students' learning motivation in Islamic Religious Education subjects at SMA Negeri 18 Makassar. This research uses a quantitative approach with a correlational design. The population in this study were students of SMA Negeri 18 Makassar with a sample of 92 students selected through a sampling technique. Data collection techniques were carried out using questionnaires and documentation. Data analysis used descriptive statistical analysis and multiple linear regression analysis. The results of the study indicate that the Differentiated Based Learning model has a positive and significant effect on students' learning motivation. The regression analysis shows that differentiated content, differentiated process, and differentiated product have positive contributions to learning motivation. The coefficient of determination (R²) shows that 57.7% of the variation in students' learning motivation can be explained by the DBL model, while the remaining 42.3% is influenced by other factors outside the research model. These findings indicate that the implementation of differentiated learning strategies can increase students' learning motivation in Islamic Religious Education learning.